2022
DOI: 10.1021/acs.inorgchem.1c03673
|View full text |Cite
|
Sign up to set email alerts
|

Rare-Earth-Metal-Complex-Catalyzed Hydroalkoxylation and Tandem Hydroalkoxylation/Cyclohydroamination of Isocyanates: Synthesis of Carbamates and Oxazolidinones

Abstract: Novel N,N,N-tridentate β-diketiminato rare-earth-metal dialkyl complexes LRE­(CH2SiMe3)2 [RE = Y (1a), Gd (1b), Yb (1c), Lu (1d); L = MeC­(NDipp)­CHC­(Me)­N­(CH2)2NC4H8, where Dipp = 2,6- i Pr2C6H3] have been conveniently synthesized by one step from reactions of the rare-earth-metal trialkyl complexes RE­(CH2SiMe3)3(THF)2 (THF = tetrahydrofuran) with a pyrrolidine-functionalized β-diketiminate HL, and their catalytic behaviors toward hydroalkoxylation and tandem hydroalkoxylation/cyclohydroamination of isocya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…This reflects that the substitution on the aromatic ring of isocyanates has a noticeable influence on the reaction outcome. Wang and coworkers reported that their Sc‐catalyst does not work for nitro‐substituted phenyl isocyanate, [12] but our catalyst works very well for 3‐nitro phenyl isocyanate (see Scheme 6, 6 i ). Surprisingly, in the case of 6 k , multiple products also form even after 30 h of reaction time.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…This reflects that the substitution on the aromatic ring of isocyanates has a noticeable influence on the reaction outcome. Wang and coworkers reported that their Sc‐catalyst does not work for nitro‐substituted phenyl isocyanate, [12] but our catalyst works very well for 3‐nitro phenyl isocyanate (see Scheme 6, 6 i ). Surprisingly, in the case of 6 k , multiple products also form even after 30 h of reaction time.…”
Section: Resultsmentioning
confidence: 78%
“…These methods predominantly employ transition metal-based catalysts like Ir, Pd, or coinage metals, lanthanides. [7][8][9][10][11][12][13] The interest in developing environmentally friendly and safer synthesis methods for industrial processes is steadily increasing. The abundant presence of magnesium in the Earth's crust has led to a surge in research on its application in catalytic processes, with notable contributions from research groups such as Harder, Hill,Parkin,Okuda,Rueping,Milstein,Sadow,Schäfer,Pucheault,Nembenna,Venugopal, Despite the growing use of magnesium complexes in catalysis over the past decade, their utilization has primarily been limited to hydrofunctionalization reactions involving unsaturated bonds like aldehydes, ketones, alkenes, alkynes, carbodiimides, and isocyanates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amide and lactam scaffolds are a class of substantial motifs frequently found in pharmaceuticals and naturally occurring molecules like imatinib, lenalidomide, and elmenol H. A wide range of approaches to constructing such indispensable amide bonds have been developed, ranging from conventional acylation of amines mediated by amide coupling agents , to modern strategies such as catalytic direct amidation , or visible light irradiation. , Among these studies, transition-metal-catalyzed C–H activation stands out as a simpler synthetic route for direct amidation of unactivated C–H bonds. Many transition-metal-catalyzed C–H functionalization methods require directing groups (DGs), especially transformable DGs, to enhance the regioselectivity and practicality. By the DG-assisted C–H activation strategy, selectively installing nitrogen-based functional groups (FGs) into molecules via the direct addition of C–H bonds to unsaturated polar C–N π-bonds represents the most powerful and economical method for rapid amide and lactam synthesis. We envisioned isocyanates to be particularly useful. As useful carbon synthons in organic synthesis, isocyanates have been extensively implemented in the construction of C–C bond formation for forging amides. Hence, employing isocyanates as FGs would be a more straightforward approach to the synthesis of amides.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of carbamates has been intensively studied in the last few years. [1][2][3] The interest in this type of system lies in a wide variety of applications in fields as different as medicinal chemistry 4,5 or new environmentally related materials. 3 Thus, the capture of CO 2 using ligands with amino groups that give rise to carbamates can be highlighted as a methodology for reducing greenhouse gas emissions.…”
Section: Introductionmentioning
confidence: 99%